A Comparative In Vitro Study of Antibacterial Efficacy of Propolis Gel and Aloevera as Dressings with Calcium Hydroxide intra Root Canals (Journal of Hama University, 2024)
Aim of the study : Evaluation of the effectiveness of both Propolis and Aloevera in eliminating Enterococcus faecalis germs prevalent in the root canals of extracted teeth and comparison of its anti-infective efficacy with calcium hydroxide .Materials and methods : single root canal teeth were used . the teeth were prepared with manual and rotary files then sterilized by autoclave after that, they were infected with bacterial suspension (E.faecalis) and were incubated for 24 hours . The teeth were divided into 4 groups (n1=n2=n3=n4=15) according to the type of root canal dressing . primary bacterial samples a (befor dressing) were taken from root canals by sterile file after disposal of bacterial suspension . the b (after dressing) samples were taken in the same way where the dressings were applied for 4 days . the samples (a and b) were transported to sterile Eppendorf tubes containing 1 mm sterile distilled water then after making the dilutings then were transferred to mueller hinton agar plates and were incubated for 24 hours .Colony forming units (CFU) were counted and bacterial reduction between a and b was analyzed for all groups and then compared . Results : It has been used One Way ANOVA Test for variable of the percentage of reduction in bacterial count% in research groups , and Post Hoc Tests that associated with One Way ANOVA Test for variable of the percentage of reduction in bacterial count% to study the effect of the materials used in the study on this variable in research groups .None of these dressings was able to completely eliminate the bacterial presence in canals . Calcium hydroxide had a bacterial reduction average (89.87%) , Propolis had (23.24%) , Aloe vera had (60.5%) , whereas distilled water had (13.43%) . Conclusion : Calcium hydroxide is superior to both propolis and aloe vera in the eradication of Enterococcus faecalis by applying them for 4 days
Keywords: Calcium hydroxide – Propolis – Aloe vera – Bacterial reduction – Enterococcus faecalis